2011
DOI: 10.17338/trainology.1.1_6
|View full text |Cite
|
Sign up to set email alerts
|

Association of vigorous physical activity with age-related, site-specific loss of thigh muscle in women: the HIREGASAKI study

Abstract: S keletal muscle mass, which is mostly located in the lower body, constitutes approximately 40% of fat-free body mass in young adults 1 but decreases with advancing age, especially after the fifth decade of life. 2 These age-related changes lead to a decline of strength and power, a decrease in physical performance, and disability. 3 Because the population of elderly people is growing in most countries, including Japan, the agerelated loss of skeletal muscle mass is likely to have a severe economic impact on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In a typical pattern of daily life, the anterior upper leg muscle is active for only a short period of time (1-3 h) and at relatively low intensities (3-11% of maximum voluntary isometric contraction) (18). Previously, we have shown that the duration of vigorous daily physical activity is positively correlated with anterior upper leg MT, but not with light or moderate physical activity (22). These results support our findings as well as our previous studies (12,28) that greater strain magnitude via vigorous daily activity may provide an effective osteoanabolic stimulus for men and women.…”
Section: Discussionmentioning
confidence: 95%
“…In a typical pattern of daily life, the anterior upper leg muscle is active for only a short period of time (1-3 h) and at relatively low intensities (3-11% of maximum voluntary isometric contraction) (18). Previously, we have shown that the duration of vigorous daily physical activity is positively correlated with anterior upper leg MT, but not with light or moderate physical activity (22). These results support our findings as well as our previous studies (12,28) that greater strain magnitude via vigorous daily activity may provide an effective osteoanabolic stimulus for men and women.…”
Section: Discussionmentioning
confidence: 95%
“…Muscle activation levels while walking on a downward slope and jogging are greater in the posterior upper-leg muscle compared with those in the anterior upper leg (Sawai et al 2006). In addition, a recent study reported that the ratio of anterior to posterior upper-leg MTH was inversely correlated to duration of vigorous physical activity in middle-aged and older women (Ogawa et al 2012b). Furthermore, we recently examined whether chronic vigorous exercise (master athletes) prevents site-specific upper-leg muscle loss experienced in sedentary adults and found that the anterior/posterior MTH ratio was similar between master athletes (cyclists and swimmers) and young active men (unpublished observation).…”
Section: Discussionmentioning
confidence: 99%
“…The anterior compartment (extensors) declined by 5·7% ( P = 0·005), while the posterior compartment (flexors) had a non‐statistically significant 3·2% decline ( P = 0·20). Preferential atrophy in the anterior compartment of the upper leg has since been supported by studies using larger cohorts of older adults (Ogawa et al ., ; Maden‐Wilkinson et al ., ) and is lightly a contributing factor to preferential decline in knee extensor torque in the current investigation.…”
Section: Discussionmentioning
confidence: 99%